Establishing a twin register in Sri Lanka - Sumathipala, A.; Fernando, D.J.S.; Siribaddana, S.H.; Abeysingha, M.R.N.; Jayasekara, R.W.; Dissanayake, V.H.W.; De Silva, N. (My University, 2000)
Nearly all twin registers are based in developed countries and there is no twin register in the developing world. Our objectives were to initiate the process of establishing a nationwide twin register in Sri Lanka by starting a volunteer register first and working towards a population-based register. Regular newspaper advertisements, feature articles, radio talks, and television programmes were used to publicise a competition for twins, their parents/relatives and friends requesting them to participate by sending in details of twins. The competition ran from 28 March 1997 for a period of 3 months. It offered prizes for three winners selected by drawing lots. Advertisements highlighted the objective of the competition as establishing a twin register for future research and emphasised that informed consent would be obtained for individual research projects. Those who registered comprise 4602 twin pairs (same sex: male - 1564, female - 1885; different sex - 1153), 80 sets of triplets (same sex: male - 17, female - 31; different sex - 42) and two sets of quadruplets (different sex). The oldest twins, triplets, quadruplets are 85, 46, and 5 years old, respectively; 88.0% of twins are less than 30 years old. Although others have previously used media publicity to enrol twins in twin registers, we believe this to be the first time that twins have been enrolled through competition. We have more young twins, and our gender and zygosity proportions after applying Weinburg's rule do not match the proportions expected from a volunteer twin sample. Establishing a twin register for research purposes has proved possible in a developing country.